Biomechanical characterization and modeling of human mesenchymal stem cells under compression. Issue 14 (26th October 2022) - Moghimi, Negar; Peng, Kaiyuan; Voloshin, Arkady
Abstract: The application of microelectromechanical systems (MEMS) in biomedical devices has expanded vastly over the last few decades, with MEMS devices being developed to measure different characteristics of cells. The study of cell mechanics offers valuable understanding of cell viability and functionality. Cell biomechanics approaches also facilitate the characterization of important cell and tissue behaviors. In particular, understanding of the biological response of cells to their biomechanical environment would enhance the knowledge of how cellular responses correlate to tissue level characteristics and how some diseases, such as cancer, grow in the body. This study focuses on viscoelastic modeling of the behavior of a single suspended human mesenchymal stem cell (hMSC). Mechanical properties of hMSC cells are particularly important in tissue engineering and research for the treatment of cardiovascular diseases. We evaluated the elastic and viscoelastic properties of hMSC cells using a miniaturized custom-made BioMEMS device. Our results were compared to the elastic and viscoelastic properties measured by other methods such as atomic force microscopy (AFM) and micropipette aspiration. Different approaches were applied to model the experimentally obtained force data, including elastic and Standard Linear Solid (SLS) constitutive models, and the corresponding constants were derived. These values were compared to the ones in literature that were based on micropipette aspiration and AFM methods. We then utilized a tensegrity approach to model major parts of the internal structure of the cell and treat the cell as a network of viscoelastic microtubules and microfilaments, as opposed to a simple spherical blob. The results predicted from the tensegrity model were similar to the recorded experimental data.